Measurement of the sound absorption coefficient of palm frond fiber composites with synthetic adhesives - Putri Pratiwi; Abdul Rahman; Asmara Yanto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2022)
Natural fiber composite materials have been widely applied for various purposes, one of which is reducing noise. Many efforts have been tried to reduce noise by using sound absorbing materials such as glasswool, rockwool, and gypsum as sound absorbers, but because of the high price and bad impact on health, many studies have been conducted to find materials that are practical, cheap, and abundant availability in nature, one of which is natural fiber as an alternative to commercial sound absorbing materials. In this study, we want to know the effect of the composition of palm fronds with polyester resin can affect the sound absorption of a material and the effect of composition on sound absorption. The composition of palm frond fiber and polyester resin was varied 60%:40%, 65%:35%, 70%:30%, 75%:25%, 80%:20%, 85%:15%, 90%:10%, arranged randomly with a length of 5 mm. The specimen synthesis process starts with cutting the palm fronds, decomposing the palm frond fibers so that the fibers are separated from the flesh. Acoustic testing was conducted using a single microphone impedance tube. The test results showed that the largest absorption coefficient value is 0.984 at a frequency of 1500 Hz and is obtained in materials with a composition of 70%: 30%, and for the largest acoustic impendance value is 1.714 which is found at a frequency of 500 Hz and is obtained in the composition of 85%: 15%.